DKK3 promotes adipogenic differentiation of stem cells by inhibiting Wnt/β-catenin signaling pathway related gene expression and mitochondrial autophagy function - Ze Zhang; Haohui Wei; Tao Lin; Changbin Zhao; Yongxiang Song; Yuelin Deng; Yiqing Sun; Yongxia Zhao; Qingbin Luo; Xiquan Zhang; Dexiang Zhang; Hongmei Li (Poultry Science)
ABSTRACT: Mesenchymal stem cells can differentiate into adipocyte precursor cells, and the balance of stem cell differentiation determines the quantity of adipocytes. Early-stage adipose tissue expression profiling revealed abnormal expression of DKK3 in the high-fat group. Moreover, DKK3 is enriched in the Wnt/β-catenin signaling pathway, and studies have shown that DKK3 can serve as a gene involved in early regulation of adipogenesis. Therefore, this study focuses on exploring how DKK3 regulates the molecular mechanism of adipocyte differentiation through the Wnt/β-catenin signaling pathway. In this experiment, the role of DKK3 in the differentiation of bone marrow mesenchymal stem cells into adipocyte precursors was validated using in vitro cultured chicken bone marrow mesenchymal stem cells. The results showed that overexpression of DKK3 led to a significant downregulation of Wnt/β-catenin signaling pathway-related marker gene expression (P < 0.05), a significant upregulation of adipogenic differentiation-related genes (P < 0.05), an increase in lipid droplet content, a significant increase in OD value (P < 0.05), a significant upregulation of mitochondrial oxidative respiratory-related marker gene expression (P < 0.05), and a significant downregulation of mitochondrial autophagy-related marker genes (P < 0.05). Conversely, the results were opposite after interfering with DKK3 gene expression. In this study, 4 SNP sites, including g.8419139, g.8419556, g.8419560, and g.8419598, were detected in the 7th exon of DKK3, among which the g.8419598 (C > T) site was significantly correlated with abdominal fat weight and abdominal fat rate in 100-day-old Ma Huang chickens (P < 0.001).